2020
DOI: 10.1097/md.0000000000022365
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for mild cognitive impairment in elderly people

Abstract: Background: Acupuncture has an unique role in preventing and managing mild cognitive impairment (MCI) in nonpharmaceutical therapies because of its small wound, mild pain, and high security for many years. However, there is no systematic review evaluating safety and efficacy of acupuncture for MCI in elderly people. Therefore, this study will provide a protocol to explore the effectiveness and safety of acupuncture for MCI in the elderly. Methods: Retrieval from 8 elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The combinations of points were usually used to achieve greater effects for the treatment of MCI. Systematic reviews and meta-analyses ( Deng and Wang, 2016 ; Kim et al, 2019 ; Li et al, 2020 ) indicated that the most frequently used acupuncture points for the treatment of MCI were Baihui (GV20), Fengchi (GB20), Shenting (GV24), and Sishencong (EX-HN1). Taiyang (EX-HN5), which can bring relaxation and refreshment as an acupressure point, is an ideal acupoint when treating disorders affecting the head ( Lu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The combinations of points were usually used to achieve greater effects for the treatment of MCI. Systematic reviews and meta-analyses ( Deng and Wang, 2016 ; Kim et al, 2019 ; Li et al, 2020 ) indicated that the most frequently used acupuncture points for the treatment of MCI were Baihui (GV20), Fengchi (GB20), Shenting (GV24), and Sishencong (EX-HN1). Taiyang (EX-HN5), which can bring relaxation and refreshment as an acupressure point, is an ideal acupoint when treating disorders affecting the head ( Lu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Current research results show that human cognitive function is highly correlated with the cortex such as the frontal lobe, temporal lobe, and parietal lobe [15]. Li et al [16] pointed out that acupuncture treatment could effectively improve the cerebral hemodynamics of patients and found that ReHo of the right posterior cingulate gyrus and left parahippocampal gyrus of the two groups of patients before treatment decreased, suggesting that the nerves' meta-excitability was decreased, and the local brain function activities were reduced, which indicated that ischemic damage to the cingulate gyrus and parahippocampal gyrus can lead to cognitive dysfunction [17]. e increase of ReHo in the left dorsolateral superior frontal gyrus brain area indicates that these brain areas are a functional compensation for the damaged brain area [18].…”
Section: Discussionmentioning
confidence: 97%
“…According to the AMSTAR-2 classification, 33 reviews (94%) were of critically low quality, and only one (Cochrane) review was of moderate quality. The essential factors affecting the literature quality included item 2 [only two studies (Peng et al, 2007;Li et al, 2020) "clearly stated that the review methods were established before the conduct of the review and justified any major differences from the protocol"], item 3 [only two studies (Mai and Zheng, 2015;FIGURE 4 | Forest plot of the effect of acupuncture on the clinical efficacy using fixed model. Kwon et al, 2018) "explained their selection of the study designs for inclusion in the review"], item 7 (just 1 study "provided a list of excluded studies and justified the exclusions"), and item 10 (none of the studies "reported on the sources of funding for the studies included in the review").…”
Section: Methodological Quality Of Included Reviewsmentioning
confidence: 99%
“…The 35 SRs/meta-analyses were published between 2007 and 2020. Thirty-two SRs/meta-analyses were conducted in China (Peng et al, 2007;Guo et al, 2008;Zhu and Zhang, 2009;Yuan and Zhang, 2010;Liu et al, 2011Liu et al, , 2015Liu et al, , 2018Tian et al, 2012;Cao et al, 2013Cao et al, , 2014Fang et al, 2014;Hu et al, 2014;Zhao et al, 2014;Lu et al, 2015;Mai and Zheng, 2015;Xu and Xie, 2015;Zhang et al, 2015;Zhou et al, 2015Zhou et al, , 2017Deng and Wang, 2016;Lin et al, 2016Lin et al, , 2017Xiong et al, 2016;Zou et al, 2016;Wan et al, 2017;Zhan et al, 2017;Li et al, 2018Li et al, , 2020Wu et al, 2018;Tang et al, 2020;Wang et al, 2020), and three SRs/metaanalyses were conducted in Korea (Lee et al, 2008;Kwon et al, 2018;Kim et al, 2019). Twenty-three SRs/meta-analyses (68%) were published in Chinese, and 12 (34%) were published in English.…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%